An Enhancement of the canny edge detection algorithm for edge detection application - Norman Robert R. Gellegani and Benedict Clarion U. Gesmundo. 4 0 16; 5 (2013)
u
Undergraduate Thesis: (BSCS major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2013.
Keywords: 2 -- 0; 6; 20; 20; 2